Teste dicótico de sentenças em adultos de meia idade normo-ouvintes: aplicação e valores de referência - Ferreira, Geise Corrêa (2022)
This research aimed to verify the performance of middle-aged, normal-hearing, adults in the Dichotic Sentence Test and to obtain reference measurements; to analyze and to relate the performance obtained in dichotic listening tests, with different stimuli: sentences, digits and alternate disyllables; to compare the performance in the dichotic test of middle-aged, normalhearing adults, with normal and altered dichotic digit test. The sample group consisted of 53 normal-hearing, right-handed, individuals, aged between 45 and 59 years, evaluated by means of the dichotic digits(DDT), sentence(DST) and alternate disyllables(SSW) tests. First, for the performance analysis and determination of the DST reference values, the performance of 38 individuals who presented results within the normal range in the DDT was considered, who showed, in the DST, in the divided attention stage, an average performance of 94.47% in the right ear and 68.16% in the left ear, with a significant difference between the ears. The asymmetry between ears ranged from -10% to 70%, with right-ear advantage. In the directed attention stage, the average performance was 99,74% in the right ear and 96,58% in the left ear, with statistical difference and asymmetry of up to 20% between the ears, with right-ear advantage. In the second stage of the research, the total sample group performance was considered, in which the investigation of the correlation and agreement between the three tests in the divided attention stage was carried out, in which there was a positive correlation between the left ear performance, of weak magnitude, between DDT and DST and moderate between SSW and DST, and a reasonable agreement between the tests was also verified. Finally, an comparison of the individuals' DST performance was held considering the TDD performance: middle-aged adults with normal DDT(G1) and with altered DDT(G2). In the DST performance analysis, G2 showed a lower performance in both ears in the divided and directed attentions stages compared to G1. In the divided attention stage, the average performance of the G2 individuals was 87.33% in the right ear and 56.67% in the left ear, with a significant difference between the ears. The asymmetry between ears ranged from 10% to 60%, with right-ear advantage. In the directed attention stage, the performance was 97.33% in the right ear and 95.33% in the left ear, with an asymmetry of -10% to 20% between the ears, with right-ear advantage. It is concluded as the expected performance values for this population in the divided attention stage: ≥ 90% correct answers in the right ear, ≥ 70% correct answers in the left ear; for directed attention, 100% correct answers in the right ear, ≥ 90% correct answers in the left ear. When there is asymmetry between the ears, it can be expected up to 30% in the divided attention stage and 10% in the directed one, with right-ear advantage. The three tests evaluated showed positive correlation and reasonable agreement in the divided attention stage, in the left ear. The G2 individuals presented inferior performance in the DST in relation to those of the G1.